Identification of novel loci for salt stress at the seed germination stage in soybean - Kan, Guizhen (Breed Sci, 2016)
Salt tolerance in soybean [Glycine max (L.) Merr.] at the seed germination stage is a critical determinant of stable stand establishment in saline soil. This study examined one population of 184 recombinant inbred lines (RILs, F(7:11)) derived from a cross between Kefeng1 and Nannong1138-2 and one natural population consisting of 196 soybean landraces. A total of 11 quantitative trait loci (QTLs) and 22 simple sequence repeat (SSR) loci associated with three salt tolerance indices were detected by linkage and association mapping. The SSR marker Sat_162 was found to be closely linked to the co-localized QTLs at a site 792,811 bp from the gene Glyma08g12400.1, which was verified in response to salt stress at the germination stage. Five SSR markers, Satt201, BE475343, CSSR306, Satt664 and Satt567, were co-associated with two of the salt tolerance indices, and two SSR markers, Satt156 and Satt636, were co-associated with all three salt tolerance indices. Furthermore, elite alleles and their carrier materials were identified by analyzing alleles at the loci associated with these salt tolerance indices. These results may be beneficial for the future breeding of soybean salt tolerance at the germination stage using marker-assisted selection and molecular pyramiding breeding.